VD_FINDINFO HC / 2009 / 388 vom 10. September 2009 - VD Tribunal cantonal (2009)
OBLIGATION D'ENTRETIEN, PERSONNE DIVORCÉE, POUVOIR D'EXAMEN, CONSTATATION DES FAITS, MALADIE, CHOSE JUGÉE, NON-LIEU, ENQUÊTE PÉNALE | 125 al. 1 CC, 138 al. 1 CC, 53 CO, 452 al. 2 CPC